Optimization of Conditions for Expression of Dengue Serotype 2 EDIII Protein in Escherichia coli and Immune Responses of Adjuvant-Free EDIII Ferritin Nanoparticles Against Dengue Virus in BALB/c Mice - M.S.B.W.T.M. Nipuna Sudaraka Tennakoon; Kyoung-Ho Lee; Hye-Mi Lee; Jae-Yeon Park; Hyun-Jin Shin (Viruses)
Self-assembling ferritin nanoparticle technology is a widely used vaccine development platform for enhancing the efficacy of subunit vaccines by displaying multiple antigens on nanocages. The dengue virus (DENV) envelope domain III (EDIII) protein, the most promising antigen for DENV, has been applied in vaccine development, and it is essential to evaluate the relative immunogenicity of the EDIII protein and EDIII-conjugated ferritin to show the efficiency of the ferritin delivery system compared with EDIII. In this study, we optimized the conditions for the expression of the EDIII protein in E. coli, protein purification, and refolding, and these optimization techniques were applied for the purification of EDIII ferritin nanoparticles. Thus, purified DENV2 EDIII and EDIII human ferritin heavy chain nanoparticles were immunized intramuscularly into BALB/c mice without an adjuvant, and the immunogenicity was analyzed using IgG ELISA and a serum-neutralizing assay. Purified, properly refolded, aggregate-free EDIII and EDIII ferritin proteins were obtained, and ferritin nanoparticles were identified using an electron microscope. By analyzing the immunogenicity of mouse serum, EDIII ferritin generated significantly higher IgG responses and neutralizing activity than EDIII-immunized mice. The IgG ELISA results confirmed that EDIII ferritin can induce a significantly higher IgG titer (O.D.:1.8) than EDIII (O.D.:0.05). Furthermore, EDIII ferritin produced a neutralizing titer of 1:68, whereas EDIII protein produced an average titer of 1:16, which is the serum dilution that inhibited 90% of the viruses. The longevity of the immune responses was analyzed using the serum obtained 2 months after the final immunization, and the results confirmed that EDIII ferritin induced constant immunity throughout the period.